Analysis of Substantial, Procedural, and Technical Aspects in the Drafting of Legislation in Indonesia - Maisondra, Maisondra; Sulaiman, Abdullah (Journal of Legal and Cultural Analytics, 2025)
The post-reform Indonesian legal system is characterized by hyper-regulation and disharmony in legislation. This study aims to analyze systemic weaknesses in the legislative drafting process that contribute to legal uncertainty and ineffectiveness. Weaknesses are identified in three main aspects: Substantive Aspects (harmonization), Procedural Aspects (participation and planning), and Technical Aspects (quality of Legal Drafting). The study results indicate that the dominance of sectoral approaches, minimal inter-institutional coordination, and the low quality of human resources for drafting are the main factors behind this acute legislative flaw. These weaknesses have serious impacts on legal certainty, the effectiveness of public policy, and the investment climate. This article examines the root causes of substantive, procedural, and technical problems in the drafting of legislation in Indonesia, referring to Law No. 12 of 2011 (and its amendments) concerning the Formation of Legislation.